Assessment of Poverty and Environmental Degradation Among Rural Communities in Billiri Local Government Area of Gombe State, Nigeria - Iliya, Musa; Babagana, Boso; Idoma, Kim (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Poverty and environmental degradation are intertwined challenges that significantly impact communities in Nigeria and across the globe. This study examined poverty and environmental degradation among rural communities in Billiri Local Government area of Gombe state, Nigeria. Random sampling was used to select seven (7) communities in Billiri Local Government area namely; Baganje, Billiri, Kalmai, Tal, Tanglang, Todi, and Tudun Kuka respectively for the study. A sample population size of 360 respondents was used for the study. The socio-demographic characteristics of the respondents indicated that the study area is dominated by male 64% while female were 31%, age group between 25 – 54 (69%) dominates, 78% of the respondents had secondary to tertiary level of education, 60% of the respondents are married, 46% of the respondents were farmers with farming experience of between 6 – 20 plus (49%). The findings revealed that the respondents have good perceptions of poverty, based on five point likert scale eight questionnaire items were used to gauge their perceptions, the perceptions indicated agreed to strongly agree. Similarly, on their perception on environmental degradation the result indicated strongly agreed to all the eight questionnaire items. Perception on land management practices in the area, the result shows that 44% which is the dominant practiced crop rotation, 18% mixed cropping while other practices were insignificant. On the effect of poverty on land management practices, 28% reported limited access to extension services and 27% inadequate fund as the principal issues. 51% assert that soil fertility has greatly reduced and 58% affirmed increase in soil erosion in the communities. The results further, indicates that 26% of the respondents reported lack awareness, 20% lack of enforcement of land management practices and 17% insufficient fund were the principal challenges. The study recommended increased access to information and awareness on poverty and environmental degradation, increased access to financial resources through micro finance programs, afforestation and reforestation particularly planting of fruits and economics trees.